Palm Kernel Cake Oligosaccharides Acute Toxicity and Effects on Nitric Oxide Levels Using a Zebrafish Larvae Model - Foo, Rui Qing; Ahmad, Syahida; Lai, Kok Song; Idrus, Zulkifli; Yusoff, Khatijah; Liang, Juan Boo (Frontiers in Physiology, 2020)
One of the beneficial effects of nondigestible oligosaccharides (NDOs) is their anti-inflammatory effects on host animals. While conventional animal studies require that analysis be done after samples have been taken from the host, zebrafish larvae are optically transparent upon hatching and this provides an opportunity for observations to be made within the living zebrafish larvae. This study aimed to take advantage of the optical transparency of zebrafish larvae to study the nitric oxide (NO) reducing effects of NDOs through the use of lipopolysaccharide (LPS) from Salmonella enterica serovar (ser.) Enteritidis (S. Enteritidis) to induce cardiac NO production . Prior to running the above experiment, an acute toxicity assay was conducted in order to determine the appropriate concentration of oligosaccharides to be used. The oligosaccharides tested consisted of oligosaccharides which were extracted from palm kernel cake with a degree of polymerization (DP) equal to or less than six (OligoPKC), commercial mannanoligosaccharide (MOS) and commercial fructooligosaccharide (FOS). Acute toxicity test results revealed that the OligoPKC has a LC50 of 488.1 µg/ml while both MOS and FOS were nontoxic up to 1000 µg/ml. Results of the in vivo NO measurements revealed that all three NDO were capable of significantly reducing NO levels in LPS stimulated zebrafish embryos. In summary, at 250 µg/ml, OligoPKC was comparable to MOS and better than FOS at lowering NO in LPS induced zebrafish larvae. However, at higher doses, OligoPKC appears toxic to zebrafish larvae. This implies that the therapeutic potential of OligoPKC is limited by its toxicity.